1966
DOI: 10.1159/000179537
|View full text |Cite
|
Sign up to set email alerts
|

Renal Ammonia Balance. A Kinetic Treatment

Abstract: Ammonia is transported into, within, and out of the mammalian kidney largely by passive means; it is suggested that the transport out may be effected exclusively by non-ionic diffusion to equilibrium. The principal objectives of this communication are to present a general kinetic equation which indubitably describes correctly any steady state of renal ammonia balance, to describe by means of a first-order kinetic equation the relations necessarily obtaining between the determinants of renal ammonia balance pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The importance of acidemia has also been outlined in the intact rat with acute metabolic acidosis, whereas urine pH seemed to be meaningless (17). Moreover, no correlation was detected between ammonia production and urine pH both in dog and in man under normal acid-base balance and in chronic NH4Cl-induced acidosis (1,42,43). It has been shown that intracellular pH of rat tubular cells is linearly correlated with extracellular pH (44).…”
Section: Resultsmentioning
confidence: 98%
“…The importance of acidemia has also been outlined in the intact rat with acute metabolic acidosis, whereas urine pH seemed to be meaningless (17). Moreover, no correlation was detected between ammonia production and urine pH both in dog and in man under normal acid-base balance and in chronic NH4Cl-induced acidosis (1,42,43). It has been shown that intracellular pH of rat tubular cells is linearly correlated with extracellular pH (44).…”
Section: Resultsmentioning
confidence: 98%
“…Although the rate of ammonium production cannot be determined from the data presented in this work, an estimate of differences in the production of ammonia by renal cortical tissue in the two groups of animals can be obtained by calculating the pNH3 of the cortex. If it is true that ammonia entry into the tubule lumen is due to nonionic diffusion of the free base NH3 where protonation and entrapment occurs (30), and that NH3 is in equilibration throughout all structures located in the cortex (31,32), then given the in situ pH and ammonium concentration of fluid obtained near the end of the proximal tubule, the pNH3 of the renal cortex can be calculated with the following formula (33,34) (35) and the solubility coefficient (a) of 0.626 (34), cortical pNH3 averaged 1,267±234 mmHg X 10-6 in the RK group, twofold the value in the sham-operated group (658±70 mmHg X 10-6). If intracellular pH fell during acidosis (36) and if ammonia entry was due solely to diffusion and no increase in synthesis occurred, then one would expect that the cortical pNH3 of the RK group would be lower than that of the sham-operated group.…”
Section: Discussionmentioning
confidence: 99%